Inside Cover: Peripheral Templation‐Modulated Interconversion between an A4L6 Tetrahedral Anion Cage and A2L3 Triple Helicate with Guest Capture/Release (Angew. Chem. Int. Ed. 7/2018). Issue 7 (18th January 2018) - Bai, Xuemin; Jia, Chuandong; Zhao, Yanxia; Yang, Dong; Wang, Shi‐Cheng; Li, Anyang; Chan, Yi‐Tsu; Wang, Yao‐Yu; Yang, Xiao‐Juan; Wu, Biao
Abstract : Peripheral templation was used to stabilize an unusual A4 L6 tetrahedral cage (A=anion, L=ligand) as reported by C. Jia, B. Wu et al. in their Communication onpage 1851. The A4 L6 cage can be transformed into an A2 L3 helicate in response to different stimuli (change template, concentration, or solvent), with accompanying guest capture and release. This process is illustrated in the picture by the famous Monkey King who has the power to change the shape and size of objects by blowing magic gas. Credits: Cartoon of the Monkey King fromhttp://588ku.com/image/n‐13858873.html .